Magnetoresponsive polymer networks as adsorbents for the removal of U(VI) ions from aqueous media. (December 2017) - Ilia, Rafaella; Liatsou, Ioanna; Savva, Ioanna; Vasile, Eugenia; Vekas, Ladislau; Marinica, Oana; Mpekris, Fotios; Pashalidis, Ioannis; Krasia-Christoforou, Theodora
Graphical abstract: Highlights: Synthesis of superparamagnetic and pH-responsive methacrylic polymer networks. Evaluation of the networks' efficiency in adsorbing U(VI) from aqueous media. Increased U(VI) adsorption efficiency by the polymer networks at acidic pH. Self-buffering of the magnetite-loaded networks at pH 8 and U(VI) binding. Abstract: Magnetoresponsive, methacrylate-based 3D polymer networks containing hydrophilic/thermoresponsive, hydrophilic/pH-responsive and hydrophobic/metal chelating functionalities and oleic acid-coated magnetite nanoparticles, have been synthesized by conventional crosslinking radical polymerization and further evaluated as adsorbents for the removal of U(VI) ions from aqueous media. The adsorption properties of the networks prior and after magnetization regarding U(VI) ion removal from aqueous solutions of varying acidity and initial U(VI) concentration have been investigated. The effect of pH on the interaction of the adsorbents with U(VI) ions was shown to differ dramatically depending on solid phase composition, due to the fact that in the magnetite-loaded network, the Fe3 O4 nanoparticles act as buffers by binding solution protons. Nevertheless, U(VI) adsorption on both types of adsorbents follows the Langmuir adsorption isotherm and the value of their maximum adsorption capacity is qmax = ∼0.02 mol kg −1 showing no statistically significant differences. The magnetic properties of these materials make their removal and adsorbed uranium separation from the aqueous phase quite simple by using an external magnetic field.